Fracture Toughness of Laser Stake Welds in Shipbuilding Industry - G. Socha; P. Kujala (Engineering Transactions, 2015)
A new technology of stake welding with the use of high power lasers was developed in the framework of EU research program "Advanced Welding for Closed Structures". This technology enable welding from outside of closed profiles due to high penetration of laser beam into the material. More than 650 static, fracture toughness and fatigue tests were performed during the research program to investigate strength of such welds. In this paper, investigations of static strength and fracture toughness are presented, results of fatigue testing will be reported elsewhere. As the result of the tensile and bend tests, very good strength and ductility of fusion zone (FZ) and heat-affected zone (HAZ) were found. Also the fracture toughness in lowered temperature was found to be satisfactory. Both traditional impact (Charpy) test and modern methods of measuring the crack tip opening displacement (CTOD) were utilised, and their results in the form of tearing energy per unit surface were compared. Also fatigue crack growth rate (FCGR) tests were performed at the constant AK value, the crack was propagating in the direction transversal to the weld midline. This technique allowed the observation of FCGR variations in different zones of the welded joint.